Evaluasi Usability dan Perbaikan Rancangan Antarmuka Pengguna Situs Website Jurusan Teknik Kimia Universitas Brawijaya Dengan Menggunakan Metode Human Centered Design (HCD) - Tri Kantun Erestini; Retno Indah Rokhmawati; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Chemical Engineering Department is one of department known as a part of Engineering Faculty in Brawijaya University. There are 5 pages on its website which everyone able to access such as Homepage, History Profile, Student Achievements, detailed information of Student Achievements in 2016, and Laboratory Facilities. The outline of problem occured during interview is an information buildup, some thick content placement, lack of information explanation from displayed image, inconsistent language and font usage, less precise colour mix used for website component, detail loss on existed link, ineffective information examination and limited menu navigation. Referred method which is used for improving interface design of Chemical Engineering Department website is Human Centered Design (HCD). HCD is a method applied to design newest solution, conforming on user requirement. Thereafter do the usability testing on the first and last evaluation. There are 3 metric usability used as parameters of success: Effectivity, Efficiency, and Satisfaction. Result shown for Success 70%, Non Critical Error 22.5%, and Critical Error 7.5%. Efficiency metric enhance 22% after website improvement. Therefore satisfaction aspect for an improved interface design reach "Acceptable" grade.